IJCM_139A: Prevalence of Hypertension among the Urban Adolescents: A Prospective Robust Survey - Revadi G; Maheshwari Mahesh; Yadav Amit Kumar; Bhaskar Smriti; Jaison Akhil; Pakhare Abhijit P (Wolters Kluwer Medknow Publications, 2024)
Background: Childhood Blood pressure (BP) is a strong indicator of adult blood pressure (BP), hence, early detection and intervention is important in adolescents. Studies from China and United States have shown BP in adolescents to be variable and has indeed outlined the need to obtain three separate readings before diagnosing hypertension. There is a dearth of this documentation of blood pressure readings at different occasions in adolescents from the Indian settings. Objective: To determine the prevalence of elevated blood pressure and hypertension among 10-18 years school going adolescents. Methodology: This was a prospective longitudinal study conducted across the five urban schools of Bhopal amongst 10-18 years adolescents. Multistage cluster sampling was adopted to cover an estimated sample size of 780 over a one-year period. Those adolescents who were present during the time of survey following their parent's consent were included. Those who were absent at two occasions during the follow up visit and those who were diagnosed with secondary hypertension were excluded. Those who satisfied the study criteria were given a self-administered WHO STEPS questionnaire initially. The height and weight were obtained followed by measurement of three auscultatory BP readings at an interval of one week apart (American Academy of paediatrics (Updated guidelines 2017) in each student. The R shiny app calculator was used for classifying hypertension in adolescents. The study was funded by AIIMS Bhopal and ethical clearance was obtained from the institute. Results: The overall prevalence of elevated BP/hypertension in adolescents was 1.4% (N=795). There was a positive correlation between BMI and (SBP & DBP). The generalised linear mixed model showed age, BMI and boys to have higher predisposition to elevated BP/HTN. There was a significant difference in the SBP and DBP between the 3 visits stratified by sex. Also, the change in SBP and DBP between the readings were significant by ANOVA. Conclusion: The prevalence of elevated BP/HTN was 1.4% with girls being protective for girls. The study cannot be generalised as it is limited to the Government schools with relatively small sample size.